Template directed synthesis of half condensed Schiff base complexes of Cu(II) and Co(III): Structural and magnetic studies. (15th May 2019) - Pandey, Priyanka; Verma, Abhineet; Bretosh, Kateryna; Sutter, Jean-Pascal; Sunkari, Sailaja S.
Graphical abstract: The formation of two new half condensed Schiff base complexes, [CuL(µ1, 1-N3 )]2 (1 ) and [CoL2 ]N3 ·H2 O (2 ) where L = (E)-2-((2-aminoethyl)methyl)-4-chlorophenol, under the templating effect of a metal ion are reported. These new complexes have been structurally and analytically characterised. Complex1 is an asymmetric µ-1, 1 azide bridged dimer displaying weak antiferromagnetic interactions ( J = −2.93 ± 0.03 cm −1 ), in agreement with the axial-equatorial N3 -linkage between the two copper centers. Complex2 is a monomer of a low spin Co(III) ion. The examples provide a direction towards the deliberate synthesis of half condensed Schiff base complexes, whose structural and magnetic studies might be interesting for molecular magnetism studies. Abstract: By the proper choice of the substituents on the aldehyde and amine groups, the nature of the Schiff base formed (fully condensed or half condensed) can be tuned by the templating effect of the metal ion. The condensation of 5-chlorosalicylaldehyde with ethylene diamine in the presence of Co(II) or Cu(II) cations and azido anions has afforded two new half condensed Schiff base metal complexes [CuL(µ1, 1-N3 )]2 (1 ) and [CoL2 ]N3 ·H2 O (2 ), where L = (E)-2-((2-aminoethyl)methyl)-4-chlorophenol, that were structurally characterized by X-ray analysis, IR and UV spectra. Complex1 is an asymmetric µ-1, 1 azide bridged dimer displaying weak antiferromagnetic interactions ( J = −2.93 ± 0.03 cm −1 ), in agreement with the axial-equatorial N3 -linkage between the two copper centers. Complex2 is a monomer of a low spin Co(III) ion.